A katG S315T or an ahpC promoter mutation mediate Mycobacterium tuberculosis resistance to 2-thiophen carboxylic acid hydrazide, an inhibitor resembling the anti-tubercular drugs Isoniazid and Ethionamide - Franceschelli, Jorgelina Judith (2018)
Clinical isolates of Mycobacterium tuberculosis and Mycobacterium bovis are differentially susceptible to 2-Thiophen Hydrazide (TCH); however its mechanism of action or the reasons for that difference are unknown. We report herein that under our experimental conditions, TCH inhibits M. tuberculosis in solid but not in liquid medium, and that in spite of resembling Isoniazid and Ethionamide, it does not affect mycolic acid synthesis. To understand the mechanisms of action of TCH we isolated M. tuberculosis TCH resistant mutants which fell into two groups; one resistant to TCH and Isoniazid but not to Ethionamide or Triclosan, and the other resistant only to TCH with no, or marginal, cross resistance to Isoniazid. A S315T katG mutation conferred resistance to TCH while katG expression from a plasmid reduced M. tuberculosis MIC to this drug, suggesting a possible involvement of KatG in TCH activation. Whole genome sequencing of mutants from this second group revealed a single mutation in the alkylhydroperoxide reductase ahpC promoter locus in half of the mutants, while the remaining contained mutations in dispensable genes. This is the first report of the genetics underlying the action of TCH and of the involvement of ahpC as the sole basis for resistance to an anti-tubercular compound.